Stable Isotope Dietary Analysis on Human Remains: A case Study at Khirbet Aqabet Al Qadi Burial Chamber, Nablus, Palestine. Issue 4 (August 2019) - Alsaud, Loay Abu; Shawamra, Awni; Qobbaj, Amer; Yasin, Jehad; Al-Khateeb, Mohammad; Issa, Abdul Khaliq; Peraza, Alfonso Fanjul; de Dios, Verónica Pérez
ABSTRACT: In 2016, a burial chamber hewn into limestone was discovered at Khirbet Aqabet Al Qadi on the northwestern slope of Mount Ebal, 2km north of the city center of Nablus. The floor of the chamber is 3.15 × 2.9 m and the height averages 1.8 m. A movable closure at the entrance consists of a limestone slab. The burial chamber houses four sarcophagi. The aim of this case study is to give information not only on the burial chamber but also, for the first time in the region, on human remains. Stable isotope analysis of a human bone sample enabled us to obtain dietary information on one individual. Due to low collagen content, the sample did not allow precise dating but it can be placed between 50 BC and 50 AD. Systematic illegal excavation and looting at funerary sites in the Nablus area has caused material for potential information to be missing at the site. Nonetheless, the dietary information obtained supports other material finds indicating Mediterranean agricultural use of the land. Our evidence demonstrates that the site dates to between the 1st and 3rd centuries AD.